Product Packaging Training to Increase MSME Sales in Karangrejo Village, Manyar District, Gresik Regency - Ainiyatuz Zakhiroh; Wiwik Saidatur Rolianah; Nurul Istifadhoh; Kholid Albar; Muhammad Yusuf Aria Widjaja (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
This article is a form of community service that seeks to solve the problems faced by micro, small and medium enterprises in Karangrejo Village, Manyar District, Gresik Regency, from the aspect of product packaging and the form of increasing sales. The solution for this program is the provision of material on the importance of packaging and packaging training. The form of activity is in the form of providing material in which MSME actors will be introduced to good and attractive branding strategies (packaging and labeling), choosing the type of packaging that suits the product, as well as selecting designs and giving labels/brands so that the product looks better and more informative. While the mentoring method is carried out by the Implementation Team for practice. The output is in the form of examples of products that are packaged and labeled in a new way.